Dynamics of intrahousehold bargaining - Joaquín Andaluz; Miriam Marcén; José Alberto Molina (Institute for the Study of Labor (IZA), 2008)
This paper studies the dynamics of bargaining in an intrahousehold context. To explore long-term partner relationships, we analyse bilateral bargaining by considering that spouses take decisions sequentially. We conclude that a greater valuation of the present, rather than the future, for the spouse who takes the second decision, increases the set of possible sustainable agreements, as well as the proportion of time that this agent devotes to a family good.
urn:nbn:de:101:1-2008112698
Keywords: C71; 330; Family bargaining; Stackelberg game; family good; Familienökonomik; Verhandlungstheorie; Extensives Spiel; Theorie